Cultural Da'wah Movement And Implementation In Civil Society - Riza Pahlevi (CV. Syntax Corporation Indonesia, 2023)
This dissertation examines the cultural da'wah movement and its implementation in civil society through a case study of Bayt al-Qur'an al-Akbar, a wooden carved structure unique to Palembang, which is the largest Bayt al-Qur'an in the world. The objective of this research is to analyze how the cultural da'wah movement is implemented through Bayt al-Qur'an al-Akbar and its impact on civil society. This study adopts a qualitative approach with a case study method. Data is collected through participatory observation, interviews with the managers of Bayt al-Qur'an al-Akbar, community members, and relevant stakeholders, as well as document analysis. Data analysis is conducted using a descriptive approach. The findings of this research reveal that the cultural da'wah movement through Bayt al-Qur'an al-Akbar has successfully integrated religious, artistic, and cultural values in the effort to disseminate the messages of Islam to the community. The implementation of cultural da'wah is evident in the architectural design of the building, combining Islamic elements with the distinctive wood carving motifs of Palembang. Additionally, Bayt al-Qur'an al-Akbar serves as a center for educational activities, awareness-raising, and religious discussions to enhance the community's understanding of Islam. The impact of the implementation of the cultural da'wah movement is evident in civil society. Bayt al-Qur'an al-Akbar has become a symbol of religious and cultural identity for the people of Palembang. Its presence contributes to building religious awareness, strengthening social networks, and enhancing the understanding of religious values in daily life. Furthermore, Bayt al-Qur'an al-Akbar has a positive influence on the tourism sector and local economy through increased tourist visits. In conclusion, this research emphasizes the significant role of the cultural da'wah movement through Bayt al-Qur'an al-Akbar, a wooden carved structure unique to Palembang, in disseminating religious messages, strengthening religious identity, and enhancing the community's understanding of Islam. Its implementation in civil society has a substantial impact in enriching religious, cultural, and economic aspects of the Palembang community. This study provides a comprehensive understanding of the relationship between the cultural da'wah movement, its implementation in civil society, and the role of Bayt al-Qur'an al-Akbar within the context of Palembang and its surrounding areas.